The Diagnosis and Treatment of Infantile Nystagmus Syndrome (INS) - Sangeeta Khanna; Louis F. Dell'Osso (The Scientific World Journal)
The successful treatment of infantile nystagmus syndrome (INS) depends primarily on accurate and repeatable diagnosis of the type(s) of nystagmus present as well as their variation with gaze and convergence angles or fixating eye. Research over the past 40 years has demonstrated that the only way to achieve both is by making and analyzing ocular motility recordings. Determination of the direct effects of peripheral and central INS therapies can only be made by pre- and post-therapy comparisons of the nystagmus characteristics, specifically of the quality of the foveation periods within each cycle. If one is only interested in cosmetic improvements, diminution of the nystagmus amplitude is all that need be measured. However, if improvement of visual function is the primary goal of therapy, then measurement of the pre- and post-therapy foveation quality must be made, both in primary position and over a broad range of gaze angles. The use of the eXpanded Nystagmus Acuity Function (NAFX) on nystagmus data yields both an accurate measure of foveation quality and a prediction of maximum potential acuity for the patient's waveform. When used with the patient's measured, pre-therapy visual acuity, the NAFX demonstrates the amount of visual acuity loss that is due to sensory abnormalities, demonstrates the amount due to the nystagmus waveform, and estimates the measured post-therapy acuity for all values of improved NAFX and gaze angles measured. The ability to predict visual acuity improvement was not possible before the use of the NAFX. The failure to incorporate accurate measures of nystagmus waveform and foveation quality into their diagnostic evaluation continues to deprive patients of the best possible standard of care and results in mistaken diagnoses as well as inappropriate and, in some cases, unneeded multiple surgeries.